Дослідження та аналіз світових та вітчизняних факторів розвитку інтелектуального потенціалу підприємств машинобудівної галузі - Марчук, Леся Сергіївна (Класичний приватний університет, 2020)
У статті проводиться аналіз факторів, які впливають на розвиток інтелектуального потенціалу промислових підприємств. Досліджується структура галузі машинобудування передових країн світу з високотехнологічним рівнем виробництва. Вивчена та наведена практика реалізації форм, процесів та принципів організації виробництва машинобудівної галузі. Висвітлена роль трудових кадрів в інноваційному розвитку машинобудування як головного чинника ефективності інтелектуального потенціалу та національної економіки загалом. Особлива увага приділяється державі як вирішальному фактору розвитку машинобудування, адже є необхідність створення гідних умов із боку держави щодо успішного освоєння економічних, управлінських, технологічних, виробничих, інноваційних факторів галузі машинобудування.

The article analyzes the factors affecting the development of the intellectual potential of industrial enterprises. The structure of the engineering industry of the advanced countries of the world with a high-tech level of production is investigated. The practice of implementing the forms, processes and principles of organizing the production of the engineering industry has been studied and presented. The role of laboring personnel in the innovative development of mechanical engineering as the main factor in the effectiveness of intellectual potential and the national economy as a whole is highlighted. Particular attention is paid to the state as a decisive factor in the development of mechanical engineering, because there is a need to create decent conditions on the part of the state for the successful development of economic, managerial, technological, production, and innovative factors in mechanical engineering. The state is considered highly developed in the event that it maximally realizes the main goals of existence, namely: improving the welfare of the population and protecting its interests. Having a leader and strategic and tactical program is key to success. The following factors have a major impact on the development of the state: historical traditions – classical education – advanced science – powerful industry – advanced economy – high quality of life – sustainable development. The powerful industry of the state is an innovative production, first of all in the machine-building industry, with a high share of the added value of manufactured products to meet the needs of the domestic and foreign markets. Leadership of the world market of intellectual potential of engineering products is provided by: specialization; concentration; production cooperation; innovative commodity and pricing policies; state support; development of new markets when selling products of domestic manufacturers, etc. Growing consumer needs can only be met by high levels of production and intellectual (meaningful) work in the field of engineering and livelihoods of the general population. At the same time, it is important to study, borrow and implement good foreign experience in the development of mechanical engineering. A good example is the state policy of industrial development in China, the USA, France, Germany, Japan, Brazil, Russia, India, Singapore and several other countries.
Research and analysis of the world and domestic factors of the development of the intellectual potential of the enterprises of the engineering industry
Keywords: інновації; глобалізація; світовий ринок; передові технології; якість життя; лідерство; індустріалізація; національна економіка; intellectual potential; development factors; engineering; innovation; globalization; world market; advanced technologies; quality of life; leadership; industrialization; national economy